Selectivity in the Coextraction of Cation and Anion by Electrochemically Modulated Liquid-Liquid Extraction - Berduque, A.; Arrigan, Damien (American Chemical Society, 2006)
Electrochemistry at the interface between two immiscible electrolyte solutions has been presented as a method of electrochemically modulated liquid-liquid extraction, where ions in a mixture can be selectively partitioned as a function of the applied interfacial potential difference. In this study, a mixture comprising 4-octylbenzenesulfonate (4-OBSA-) and tetraethylammonium (TEA+) ions was evaluated. The application of negative potential differences enabled the selective extraction of 4-OBSAinto the organic phase, and more positive potential differences enabled the selective extraction of TEA+. However, intermediate potentials lead to the coextraction of both ions into the organic phase, with apparent selectivity for TEA+ over 4-OBSA-. An increased concentration of either ion in the mixture inhibited the extraction response of the other ion, but the order of the extraction at these intermediate potentials was always TEA+ followed by 4-OBSA-. The reasons for the selectivity for the cation over the anion are discussed.